Using Problem-Based Learning and Gamification as a Catalyst for Student Engagement in Data-Driven Engineering Education: A Report - Dino Čubela; Alexander Rossner; Pascal Neis (MDPI AG, 2023)
This report explores the integration of problem-based learning, gamification, and data-driven approaches in engineering education. With a focus on the course "GeoGovernment 1", this framework aimed to engage students actively and foster self-directed learning. By tackling real-world issues like automated teller machine (ATM) burglaries in Rhineland-Palatinate (Germany), students gained experience in data analyses and geoinformatics technology. This approach not only motivated students but also enhanced their prospects in science, technology, engineering, and mathematics (STEM) fields, equipping them with skills necessary for their future careers. The course structure emphasized student-centered learning, with educators playing facilitative roles to provide guidance. In summary, the combination of problem-based learning, gamification, and data-driven approaches offers a promising solution to address the challenges faced by STEM education, providing an engaging and effective learning experience for students, and ultimately preparing them for the demands of the ever-evolving professional landscape.